ChemInform Abstract: 2‐Pyridyl Thiazoles as Novel anti‐Trypanosoma cruzi Agents: Structural Design, Synthesis and Pharmacological Evaluation. Issue 12 (March 2015) - de Oliveira Cardoso, Marcos Verissimo; et al., et al.
Abstract The majority of new compounds (III) and (V) are potent cruzain inhibitors and show similar or greater trypanocidal efficacy than standard drug benznidazole, used for treatment of Chagas disease.